2013
DOI: 10.1038/gim.2012.154
|View full text |Cite
|
Sign up to set email alerts
|

The responses of research participants and their next of kin to receiving feedback of genetic test results following participation in the Australian Ovarian Cancer Study

Abstract: Purpose:The generation of clinically significant genetic data during research studies raises a number of ethical issues about the feedback of this information to research participants. Little is known about research participants' experiences of this practice.Methods: This qualitative interview study investigated research participants' (n = 10) or their nominated next of kin's (relatives) (n = 15) experiences of receiving BRCA1 and BRCA2 genetic test information following participation in the Australian Ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…In our study, all those who responded to our survey had mainly positive experiences of the process and thought that genetic results, including possible life-saving information, should be returned to the participants. However, Hallowell et al [7] reported more negative reactions, especially among 15 relatives of participants of an ovarian cancer study where the prevalence of BRCA was examined. Based on mixed experiences of breast cancer patients who were delivered BRCA findings, Richards et al [6] concluded that genetic findings should not be reported to participants in epidemiological studies, unless there are very clear and specific reasons for it.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, all those who responded to our survey had mainly positive experiences of the process and thought that genetic results, including possible life-saving information, should be returned to the participants. However, Hallowell et al [7] reported more negative reactions, especially among 15 relatives of participants of an ovarian cancer study where the prevalence of BRCA was examined. Based on mixed experiences of breast cancer patients who were delivered BRCA findings, Richards et al [6] concluded that genetic findings should not be reported to participants in epidemiological studies, unless there are very clear and specific reasons for it.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different health care systems may also influence the reactions towards predictive genetic test results. In our study, questionnaires were sent to participants over 2 years after the first information about the finding of a mutation, whereas in the Australian Ovarian Cancer Study, interviews were done only 14 weeks after the disclosure [7]. There could also be certain cultural differences, as it seems that Finnish people are more trustworthy and have more positive attitudes towards biobank studies in general when compared to other European countries [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations